Biology, comparative genomics and molecular diagnostics of Xanthomonas species infecting rice and corn - Lang, Jillian M., author; Leach, Jan E., advisor; Bush, Daniel, committee member; Reddy, Anireddy, committee member; Verdier, Valérie, committee member (Colorado State University. Libraries, 2017)
Emerging bacterial diseases on staple and economically important crops can pose critical threats to food security. Accurate identification of bacterial plant pathogens is the foundation of effective management for growers. This work advances the application of genomics to identify and characterize bacterial plant pathogens in the genus Xanthomonas that can cause destructive diseases on most agricultural crops, including rice and corn. In this thesis, taxonomy, host range, disease phenotypes and basic biology of the following pathogens were established: X. oryzae pv. oryzae, X. o. pv. oryzicola, X. o. pv. leersiae and X. vasicola pv. vasculorum. X. o. pv. oryzae and X. o. pv. oryzicola infect rice and cause bacterial blight and bacterial leaf streak, respectively. X. o. pv. leersiae infects cutgrass (Leersia sp.), weedy grasses that can serve as alternative hosts to X. oryzae and are endemic in all rice growing regions. X. vasicola pv. vasculorum was identified as the causal agent of bacterial leaf streak of corn, an emerging and now wide-spread disease in the United States, that was reported for the first time in 2017. This work established that X. vasicola pv. vasculorum can also infect sorghum and sugarcane and that the US strain is 99% similar to strains isolated over 20 years ago in S. Africa. To develop robust molecular diagnostic tools for these pathogens, unique features needed to be first identified. Using comparative genomics that included closely related bacteria and distant relatives, PCR-based diagnostic tools were developed, then validated using isolated cultures and field grown plant materials. Comparative genomics also contributed to elucidation of the taxonomy and phylogeny of X. o. pv. leersiae and X. v. pv. vasculorum. Characterization of X. o. pv. leersiae revealed adaptations to both the weedy grass hosts and rice. These features include virulence proteins that target homologous host genes (transcription activator like effectors, TALEs) to influence host gene expression. I conclude that X. oryzae is a complex that includes X. oryzae pv. oryzae, X. o. pv. oryzicola and X. o. pv. leersiae and that this complex can provide a unique window into pathogen evolution. By better understanding how pathogens adapt to their environments including new hosts, growers can manage surrounding ecosystems more effectively to minimize yield losses and therefore, contribute to food security.